PICKLING AND PASSIVATION CONVEYOR METAL SHEETS LITHOGRAPHED FOR DRYING OXIDATIVO - Reátegui S., Scila (2008)
The flow redox that forms between the metallic transporters and their surroundings, gives rise to the oxidating process of the alloy of which they are done. The application of average mechanics and chemicals remove formed oxides, contributing to their rehabilitation. Of tried acids, the spirit of salt to 20%V, was the solution that fulfilled the specifications for the removal and cleaning (pickling) of a metallic structure. Then, the formation of oxidating centers was slowed down by means of the aspersion with aqueous solution of sodium nitrite to 20%V. Also, the drying to temperatures majors of 160ºC optimizes the passivation. The results obtained to different times show a mini formation of rust, the one that to industrial conditions is despicable.